STUDI TENTANG SARANA DALAM PENINGKATAN MUTU BELAJAR PADA TAMAN KANAK -KANAK (TK) NEGERI PEMBINA LUBUK BASUNG KABUPATEN AGAM - YOZA NOVRITA, Ramalis Hakim, Yahya (Serupa The Journal of Art Education, 2013)
The purpose of this study was to describe, 1) the image quality and learning outcomes Kindergarten State Lubuk Basung cone Kabupaten Agam , 2) the use of a learning tool in improving the quality of learning that existed at State Lubuk Basung cone TK Kabupaten Agam.This study uses a descriptive qualitative method. Sources of data in this study is primary data, in the form of oral testimony from informants and secondary data from the literature library. Data collection procedures by observation, interviews and documentary study. Data were analyzed by performing data reduction (data presentation and systematically arranged so that the data obtained can explain and answer the problem under study) and draw conclusions. Checking the validity of the findings made by the technique of triangulation of sources.